Digital Teaching Practices and Student Academic Stress in the Era of Digitalization in Higher Education - Norabuena-Figueroa, Roger Pedro (2025)
ICT and digitization are transforming higher education, but one aspect that has been little addressed is student academic stress in this context. The objective of this research was to explore the relationship between teaching practices and academic stress in virtual learning environments. A quantitative study based on structural equation modeling was conducted using 6605 students from a public university in Lima. Two scales were applied and validated to assess specific dimensions of teaching practices and levels of academic stress. The scales demonstrated robust psychometric properties. Exploratory and confirmatory factor analysis allowed the identification of key underlying factors and the validation of the proposed theoretical model. Findings reveal indirect negative influences between teaching practices and academic stress. External factors like overload, distractions, and technological issues disrupt teacher interaction, collaboration, and learning processes. Model fit indices confirm its robustness, emphasizing the need to optimize resources and improve virtual education environments. ICT in education enhances accessibility and personalization but demands addressing academic stress and optimizing virtual learning environments. Future research is called for to delve deeper into the integration of emerging technologies, particularly artificial intelligence and virtual reality, as well as mindfulness, digital skills, and mobile self-efficacy, to comprehensively address stress and student well-being.